Determination of Chemically Desposited ZnO Thin Films for Possible Device Applications - Onwuemeka, J. I.; Eze, F. C.; Ndukwe, I. C. (Challenges and Advances in Chemical Science Vol. 6, 2021)
A study on the Deposition and Characterization of ZnO Thin Films by Solution Growth Technique using Ammonia (NH3) as a complexing agent. Zinc oxide thin films were successfully deposited on glass slides under certain deposition condition of 60\(^{°}\)C-100\(^{°}\)C of 1M solution of NaOH, using solution growth technique. X-ray fluorescence (XRF) and Rutherford Backscattering Spectroscopy (RBS) analyses confirmed that the films were ZnO thin films. The films of ZnO showed optical transmittance of 20.6% to 65.6% in the UV, 70.2% to 79.2% in the visible and 79.5% to 81.6% in the near-infrared regions of electromagnetic spectrum. ZnO films were found to exhibit absorbance of 25.5% to 68.6% in the UV, 10% to 18.3% in the visible region and 8.8% to 9.96% in the near-infrared regions of electromagnetic spectrum. ZnO thin films, exhibited low reflectance, throughout the electromagnetic spectrum (9.6% to 20.3%). Direct band gap values of 3.31eV is obtained for ZnO thin films. The thickness of 0.082\(μ\)m thickness was obtained for ZnO films by gravimetric method. Other properties investigated were the refractive index, optical conductivity, absorption coefficient and dielectric constants. From the spectral qualities, ZnO thin film may be found useful in heat mirror application. The sample of ZnO thin films are also found interesting as semiconductor materials for electronic applications.